The effectiveness of the intervention program on the attitude and self-concept of students with Dyslexia. - Zeinab, Mihandoost; Elias, Habibah; Mohd Nor, Sharifah; Mahmud, Rosnaini (2010)
The purpose of this study is to investigate the effect of the Barton Intervention Program on the attitude and self-concept of dyslexic students. The Dyslexia Screening Instrument (DSI), and Reading Text were employed in order to identify the dyslexic students in schools in Ilam, Iran. The population of the study included 138 dyslexic students studying in elementary schools in Ilam, Iran and from this population, 64 students were selected randomly and assigned equally to an experimental group and a control group (32 students in each group). The experimental group was taught for 36 sessions using the Barton method, in two levels, and ten lessons were provided to improve their reading skills. Reading attitude and self-concept to read instruments were employed to measure their attitude and self-concept, before and after the intervention program. The reliability of the reading attitude and self-concept were confirmed. The content validity of the scales was investigated using the judgment of 10 psychology experts. The analysis of the finding through independent t-test showed a significant difference between the control group and the experimental group after the intervention, at ρ<0.000.